Hadith #2506 - Sunan Abi Dawud - Abdur Rahman bin Abi al-Zanad عبد الرحمن بن أبي الزناد; Abu al-Zanad أبو الزناد; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Zayd ibn Thabit (Sunan Abi Dawud)
Najdah bin Nufai’ said “I asked Ibn ‘Abbas about the verse. “Unless you go forth, He will punish you with a grievous penalty.” He replied “The rain stopped from them. This was their punishment.”
Grade: Da'if

Hadith #3361 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Kharija ibn Zayd ibn Thabit خارجة بن زيد بن ثابت الأنصاري; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد; Zayd ibn Thabit (Sunan Abi Dawud)
The Prophet (ﷺ) forbade the sale of fruits on the tree for fruits by measure, and sale of grapes for raisins by measure, and sale of harvest for wheat by measure.
Grade: Sahih

Hadith #3371 - Sunan Abi Dawud - Abu al-Zanad أبو الزناد; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Anbs'h bin Khalid bin Yazid عنبسة بن خالد بن يزيد; Sahl bin Abi Hathma; Urwa ibn al-Zubayr عروة بن الزبير; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد; Zayd ibn Thabit (Sunan Abi Dawud)
The Prophet (ﷺ) forbade the sale of grapes till they became black and the sale of grain till it had become hard.
Grade: Sahih

Hadith #3406 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ja'far bin Brqan جعفر بن برقان; Thabit bin al-Hajjaj ثابت بن الحجاج; Umar bin Ayoub al-Bdy عمر بن أيوب العبدي; Zayd ibn Thabit (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: If any of you does not leave mukhabarah, he should take notice of war from Allah and His Apostle (ﷺ).
Grade: Da'if

Hadith #3558 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Tawus bin Kaysan طاوس; Zayd ibn Thabit (Sunan Abi Dawud)
The Prophet (ﷺ) said: Life-tenancy is lawful for the one to whom it is given and donation of property to go to the survivor is lawful to whom it is given.
Grade: Sahih

Hadith #3659 - Sunan Abi Dawud - Aban bin 'Uthman أبان بن عثمان بن عفان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Zayd ibn Thabit (Sunan Abi Dawud)
The Prophet (ﷺ) said: You hear (from me), and others will hear from you; and people will hear from them who heard from you.
Grade: Sahih

Hadith #3974 - Sunan Abi Dawud - Abdur Rahman bin Abi al-Zanad عبد الرحمن بن أبي الزناد; Abu al-Zanad أبو الزناد; Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور; Kharija ibn Zayd ibn Thabit خارجة بن زيد بن ثابت الأنصاري; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Zayd ibn Thabit (Sunan Abi Dawud)
The Muslims met a man with some sheep of his. He said: Peace be upon you. But they killed him and took those few sheep. Thereupon the following Qur’anic verse was revealed: “…And say to anyone who offers you a salutation: Thou art none of believer, coveting the perishable good of this life.” meaning these few sheep.
Grade: Sahih

Hadith #4271 - Sunan Abi Dawud - Abdur Rahman bin Ishaq عبد الرحمن بن إسحاق بن عبد الله; Abu al-Zanad أبو الزناد; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Mjald bin Awf مجالد بن عوف; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Zayd ibn Thabit (Sunan Abi Dawud)
I asked Yahya b. Yahya al-Ghassani about the word i’tabata bi qatlihi spoken by him (as mentioned in the previous tradition). He said: It means those people who fight during the period of commotion (fitnah), and one of them kills (the other people) presuming that he is in the right, so he does not beg pardon of Allah of that (sin). Abu Dawud said: And he said: The word fa’tabata means “he shed blood profusely”
Grade: Sahih

Hadith #4553 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; al-Qasim bin Salam القاسم بن سلام; Muhammad bin 'Abdullah bin Qahzad محمد بن عبد الله بن قهزاد; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Sa'id bin Abi Sa'id; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Zayd ibn Thabit (Sunan Abi Dawud)
The bloodwit for what resembled intentional murder should be forty pregnant she-camels in their fifth year, thirty she-camels in their fourth year, and thirty she-camels in their third year. The bloodwit for unintentional murder is thirty she-camels in their fourth year, thirty she-camels in their third year, and twenty she-camels in their second year.
Grade: Da'if